Effect of processing and storage conditions on quality of Malaysia Tualang honey - Anis Mastura binti Ahmad Fuad
Honey is produced by honeybees or stingless bees and its quality can be measured by observing the physicochemical properties. It is highly concentrated with sugar and contains mostly glucose and fructose, which will crystallise during storage that may affect the quality of honey, and influence consumers' acceptability. Conventional heating i a common treatment applied to honey to preserve its quality and facilitate packaging. The treatment will reduce the viscosity and moisture level of honey, destroy yeasts, liquefy crystals, and delay crystallisation. However, conventional heating may increase the hydroxymethyfurfural (HMF) content in honey which is a potential carcinogen to human and lead to quality deterioration. Alternatively, the use of microwave and ultrasound to treat honey can minimize the heat exposure. This study was conducted to determine the influence of storage time and temperature on the quality of selected Malaysian honey, to evaluate the quality of honey treated with different techniques, and to investigate the effect of thermal treatment on its quality during storage. The quality of honey was determined from physical analysis (turbidity, colour, pH, water activity, and m isture content), crystallization behaviour using Differential Scanning Calorimeter (DSC), sugar composition by using a High Performance Liquid Chromatography (HPLC), and HMF analysis using White method. Initially, Tualang, Kelulut, Gelam, and Acacia honeys were stored at different temperatures (-20,4 and 25 °C) up to 180 days. The selected samples were then treated at different conditions; 50- 90°C for 1-60 min using conventional heating, 100-1000 W for 10-60 s using microwave, and 50-90% amplitude for 10-30 min using ultrasound technique. The formation of crystals in Tualang honey was the greatest at 4 °C as the area under the DSC curve was the widest. Based on the results, Tualang honey was chosen to be further analysed after being treated with different techniques. The best condition for each treatment was determined at 70°C for 15 min using conventional heating, 550 W for 10 s for microwave treatment, and 70% amplitude for 10 min using ultrasound treatment. This study also points out that the use of ultrasound treatment slowed down the HMF formation compared to conventional heating and microwave treatment. However, conventional heating was selected for storage study at 4 and 25°C for 180 days as it was a common practice among honey producers in Malaysia. After 180 days, there was no visible crystals were formed in samples stored at both storage temperatures. Heat treatment apparently could maintain the quality of Tualang honey by inhibiting the crystallisation process. Moreover, it can be highlighted that 4°C was the most preferable temperature to store Tualang honey as the increment ofHMF value was slower than 25 °C, thus it can maintain the quality of honey for a longer period of time.